2021
DOI: 10.3946/kjme.2021.185
|View full text |Cite
|
Sign up to set email alerts
|

Exploring medical educators’ readiness and the priority of their educational needs for online teaching

Abstract: Purpose This study investigated medical educators’ readiness for online teaching by exploring their perceived ability and importance of online teaching competencies and identified the highest priority of their educational needs. Methods In this study, 144 medical education faculty members from a university were invited to participate. The faculty online teaching readiness scale was virtually distributed at the end of the spring semester of 2020 and 38 faculty members re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Studies found that teachers' readiness was low, especially in online learning and course design. [9][10][11] The lack of preparation, compounded by the student's rapid transition from on-campus learning to the home environment, presented additional stress that affected their academic performance, mental health and social life. 7 12 Several studies have reported the impact of COVID-19 on medical students.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies found that teachers' readiness was low, especially in online learning and course design. [9][10][11] The lack of preparation, compounded by the student's rapid transition from on-campus learning to the home environment, presented additional stress that affected their academic performance, mental health and social life. 7 12 Several studies have reported the impact of COVID-19 on medical students.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, most teachers were not trained in online learning and were not used to distance learning pedagogies. Studies found that teachers’ readiness was low, especially in online learning and course design 9–11. The lack of preparation, compounded by the student’s rapid transition from on-campus learning to the home environment, presented additional stress that affected their academic performance, mental health and social life 7 12…”
Section: Introductionmentioning
confidence: 99%
“…In response to the COVID-19 pandemic, universities around the world moved to online teaching and learning. This transition was rapid, with minimal or no staff preparation (Si et al, 2021), and is known to have caused significant challenges for educators who have typically delivered teaching within traditional face-to-face settings (Hofer et al, 2021;Forbes et al, 2021;Shih et al, 2020;Si et al, 2021;Smyth et al, 2012;von Keyserlingk, 2021). Whilst such COVID-safe measures were mandated relatively simultaneously around the globe, they have receded at differing rates internationally.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences of university educators whilst teaching online have been explored (Si et al, 2021). Without prior exposure to an online setting, educators tend to transfer their traditional pedagogies to online classrooms (Si et al, 2021), which is reported to be suboptimal for student learning (Baran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation